Modeling of simple pump system using MATLAB/Simulink / Mohd Shahrul Amin Mohd Tohid - Mohd Tohid, Mohd Shahrul Amin (2007)
The thesis presents a simulated study of simple pump system performance characteristics using MATLAB/SIMULINK software. The developed SIMULINK model enables both the dynamic and steady-state operating condition characteristics of the pump system, such torque, current and speed to be determined and analyzed. The understandings of the performance characteristics are crucial in the process of designing and selection of proper specification of motor and protection devices. This is because it enables accurate prediction of highest possible magnitude of peak performance characteristics to be made. Analysis performed on the obtained simulated results at different load level of operations enables optimization operation of the pump system to be determined and subsequently will lead to the operation of the system with much better energy-saving capability.